Selenium for acute watery diarrhea in children - Meiviliani Sinaga; Supriatmo Supriatmo; Rita Evalina; Ade Rachmat Yudiyanto; Atan Baas Sinuhaji (Paediatrica Indonesiana, 2016)
Background Acute watery diarrhea remains a major health problem affecting infants and children in developing countries. Selenium deficiency may be a risk factor for diarrhea and vice versa. Few studies have been conducted on the effectiveness of selenium for the treatment of diarrhea in children.Objective To determine the effectiveness of selenium in reducing the severity of acute watery diarrhea in children.Methods A single-blind, randomized clinical trial was done in children with acute watery diarrhea, aged six months to two years, and who visited the community health center in Simalungun from May to August 2012. Children were randomized into either the selenium or placebo (maltodextrin) group. We monitored diarrheal frequency, stool consistency, and duration of diarrhea. Mann-Whitney, Fisher’s, and Kolmogorov-Smirnov tests were used to compare the two groups.Results Sixty-five children were recruited into the study, of whom 36 children received selenium and 29 children received a placebo. The selenium group had significantly lower frequency of diarrhea (bouts per day) than the placebo group on days 2, 3, and 4 after treatment onset [day 2: 3.5 vs. 4.1, respectively (P=0.016); day 3: 2.7 vs. 3.4, respectively (P=0.002); day 4: 2.1 vs. 2.8, respectively (P<0.001)]. On day 2, stool consistency had significantly improved in the selenium group compared to the placebo group (P=0.034). In addition, the median duration of diarrhea was significantly lower in the selenium group than in the placebo group (60 vs. 72 hours, respectively; P=0.001). Median recovery time from the the first day of diarrhea was also significantly lower in the selenium group than in the placebo group (108 vs. 120 hours, respectively; P=0.009).Conclusion In children with acute watery diarrhea, those treated with selenium have decreased frequency of diarrhea, improved stool consistency, as well as shorter duration of diarrhea and recovery time than those treated with a placebo. [Paediatr Indones. 2016;56:139-43.].